Hyperbilirubinemia decreases physiological markers in adjuvant-induced arthritis - Bauerova, K; Drafi, F; Kuncirova, V; Ponist, S; Mihalova, D; Babal, P; Sykora, T (Physiological research, 2015)
There is evidence that a higher serum level of bilirubin (BIL) may be a protective factor for autoimmune diseases. We examined the effect of BIL supplementation in adjuvant-induced arthritis (AIA) where oxidative stress, inflammation and inadequate immune response are present. Male Lewis rats were randomized into groups: CO - control, AIA - untreated adjuvant-induced arthritis, AIA-BIL - adjuvant-induced arthritis administrated BIL (200 mg/kg b.w. daily i.p. during 14 days). Change of hind paw volume in the AIA-BIL group in comparison to the AIA group was significantly decreased after BIL administration. In CO and AIA groups we found almost untraceable levels of BIL. In the AIA-BIL group hyperbilirubinemia was observed. BIL administration significantly decreased plasma levels of C-reactive protein and ceruloplasmin in the AIA-BIL group in comparison to the AIA group. The values of white and red blood cells, hemoglobin and hematocrit were significantly decreased in AIA-BIL after BIL supplementation. Organs like spleen and thymus had a lower weight in AIA-BIL than in AIA. Histological findings showed decreased or even absent damage in hind paw joint of AIA-BIL animals. We observed an immunomodulatory effect of BIL on AIA development, which may also have a novel pharmacological impact.
Keywords: Animals; artritida experimentální; Rats; hyperbilirubinemie; Hyperbilirubinemia; potkani inbrední LEW; Biomarkers; Arthritis, Experimental; Rats, Inbred Lew; Male; biologické markery; mužské pohlaví; Bilirubin; krysa rodu Rattus; zvířata; bilirubin